Peran Musik dalam Regulasi Emosi dan Perubahan Mood : Kajian Literatur - Aisyah Khamini; Tri Setyo Andri Maulana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Music is a phenomenon that not only serves as entertainment but also plays a role in stabilizing an individual's emotions and mood. This study aims to examine the role of music in helping manage emotions and its influence on mood through a literature review approach. The method of this research is literature review with content analysis of various previous studies which is relevant in the field of music psychology, significantly contribute to helping individuals for express emotions, reducing negative emotions such as stress and anxiety. In addition, musical characteristics such as melodic tempo and personal meaning have been shown to influence mood changes through psychological mechanisms such as memory associations, emotional contagion, and affective cognitive responses. These findings confirm that music has the potential as a supporting therapeutic in managing emotions and individual psychological well-being